2018
DOI: 10.15294/jda.v10i1.12878
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pyramidal Ownership Structure to the Financing Policies and Firm Value in Indonesia: Cronyman as Moderating Variable

Abstract: The research to examine the effects of ownership structures on financing policies and firm valuation. The populations are all listed companies in Indonesia Stock Exchange for period of 2013 and 2015. The sample selection technique used purposive sampling and resulting in a final sample of 72 listed firms. Empirical tests are conducted using multiple regressions and two stages least squares regression to test the simultaneous relationship between ownership structure, financing policies and firm value. The estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Menurut penelitian yang dilakukan oleh Budiyanti et al (2018), menemukan bahwa struktur kepemilikan piramidal dapat mempengaruhi kebijakan pendanaan perusahaan. Leverage yang berlebihan dapat digunakan oleh perusahaan-perusahaan piramida untuk mempertahankan kontrol pemilik utama.…”
Section: Pendahuluanunclassified
“…Menurut penelitian yang dilakukan oleh Budiyanti et al (2018), menemukan bahwa struktur kepemilikan piramidal dapat mempengaruhi kebijakan pendanaan perusahaan. Leverage yang berlebihan dapat digunakan oleh perusahaan-perusahaan piramida untuk mempertahankan kontrol pemilik utama.…”
Section: Pendahuluanunclassified
“…The effect of ownership concentration on firm performance has been studied by Laporšek et.al [9], Budiyanti et.al [10], Malan et.al [11] and Chen et.al [12]. Laporšek et al [9] found a significant relationship between ownership concentration and firm performance in Slovenia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Budiyanti et.al. [10] found an interrelation of pyramidal ownership structure on financial policy for Indonesian firms listed in IDX during 2013 to 2015. Malan et.al [11] found a dominant controlling role of majority shareholder in Malaysia during 1990 to 2010, which expropriate minority shareholder.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation